2015
DOI: 10.1002/mnfr.201500161
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of eicosapentaenioic and docosahexaenoic acids into breast adipose tissue of women at high risk of breast cancer: A randomized clinical trial of dietary fish and n‐3 fatty acid capsules

Abstract: Fish provides an excellent source of n-3 PUFAs that increases breast adipose EPA, DHA similar to supplements and represents a well-tolerated intervention for future studies of the impact of n-3 PUFAs and dietary patterns on breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
12
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 39 publications
5
12
0
1
Order By: Relevance
“…The same conclusion was reached by a meta-analysis of data from 21 independent prospective cohort studies [3]. Moreover, the association of n-3 LC-PUFAs and the incidence of several cancer types have been highlighted by numerous epidemiological studies [4][5][6][7][8]. In addition to that, n-3 LC-PUFAs intake is associated with positive effects on cardiovascular health [9][10][11], brain function [12,13], immunity [14], and inflammation [15].…”
Section: Introductionmentioning
confidence: 58%
“…The same conclusion was reached by a meta-analysis of data from 21 independent prospective cohort studies [3]. Moreover, the association of n-3 LC-PUFAs and the incidence of several cancer types have been highlighted by numerous epidemiological studies [4][5][6][7][8]. In addition to that, n-3 LC-PUFAs intake is associated with positive effects on cardiovascular health [9][10][11], brain function [12,13], immunity [14], and inflammation [15].…”
Section: Introductionmentioning
confidence: 58%
“…Evidence from meta-analyses of Yang et al [53] and Nindrea et al [54] clearly confirms that higher intake ratio of n-3/n-6 PUFAs is associated with lower risk of breast cancer among females, which implies breast cancer prevention and treatment might be possible through increasing dietary intake ratio of n-3/n-6 PUFA. Additionally, Straka et al [55] and Maillard et al [56] observed increased accumulation of C20:5, c,c,c,c,c-∆5,8,11,14,17 and C22:6, c,c,c,c,c,c-∆4,7,10,13,16,19 in breast adipose tissue of women at high risk of breast cancer; the accumulation resulted from both diet supplementation and increased fish consumption. These results are in line with numerous studies demonstrating anticarcinogenic properties of long chain PUFA [36,57,58].…”
Section: Discussionmentioning
confidence: 99%
“…Associations have also been found between the fatty acid composition of erythrocyte membranes and the risk of colon cancer, colon adenomas, breast cancer and non-Hodgkin's lymphoma. 18,33,[36][37][38] Some studies have highlighted changes in the fatty acid composition of the erythrocyte membranes of cirrhotic patients. 24,30,39,40 For example, Guarini et al 24 .…”
Section: Discussionmentioning
confidence: 99%